PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, KINERJA LINGKUNGAN, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE 2013-2015) (JURNAL EKONOMI AL-KHITMAH, 2019)
This study is an empirical study of the financial performance of companies in manufacturing companies listed on the Indonesian stock exchange (IDX). This study aims to prove the effect of disclosure of corporate social responsibility (CSR), environmental performance, company size on the company's financial performance. The design of this study is causal associative research (causal relations). The data used in this study are quantitative data. The population in this study is a company included in a manufacturing company in the Indonesian stock exchange for the period 2013-2015. Sampling is done through purposive sampling. Data analysis used a simple and multiple linear regression method using SPSS version 22. The results of this study state that disclosure of corporate social responsibility (CSR) does not affect the company's financial performance, environmental performance does not affect the company's financial performance, and the size of the company has an influence on the company's financial performance.